November of the heart [large type] - Spencer, LaVyrle (G.K. Hall large print book series., 1993)
The White Bear Yacht Club is the setting for this Victorian-era romance between a wealthy young woman, Lorna, and her father's servant, Jens. He offers his boatbuilding skills to help Lorna's father win a coveted race, but when his passionate encounters with Lorna are discovered they are both in jeopardy.